More Than Just Water: The Role of CSR in Building Trust in Short and Long Term Toward AQUA in Surabaya - Potu, Tania Monica; Liao, Yi-Chuan; Gunawan, Hananiel Mennoverdi; Siahaya, Janice Carysa (International Ecsis Association, 2025)
Corporate Social Responsibility (CSR) has evolved from a peripheral activity into a strategic component of sustainable business management, particularly in industries where consumer values are closely tied to ethical and environmental considerations. In Indonesia’s bottled water sector, CSR initiatives are increasingly recognized as instruments for building consumer trust and strengthening long-term brand relationships. This study aims to examine how CSR influences short-term and long-term consumer responses—specifically purchase intention and client loyalty—through the mediating role of brand trust. It further seeks to identify which CSR dimensions most effectively drive consumer trust and sustained behavioral engagement. A quantitative research design was employed using purposive sampling among 100 AQUA consumers in Surabaya. Data were collected through structured Likert-scale questionnaires and analyzed using SPSS version 22, including validity, reliability, and regression analyses to test the causal relationships among CSR, brand trust, buying intention, and loyalty. The results reveal that CSR exerts a significant positive impact on brand trust (β = 0.605), which subsequently influences both short-term purchasing intentions (β = 0.480) and long-term loyalty (β = 0.855). While CSR’s direct impact on immediate purchasing behavior is moderate, its influence on sustained loyalty is substantial. Theoretically, this research advances CSR literature by distinguishing temporal effects on consumer behavior. Practically, it underscores CSR’s strategic potential as a brand differentiation mechanism that fosters trust, loyalty, and emotional connection in competitive markets.